The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.2151/jmsj.2019-036
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Processes for Heavy Rainfall in the Early Morning over the Korean Peninsula during Episodes of Cloud Clusters Associated with Mesoscale Troughs

Abstract: An investigation has been carried out using rainfall observation data, an analysis and forecast data by National Centers for Environmental Prediction (NCEP) Climate Forecast System Reanalysis (CFSR) to explain the environment and processes that lead to heavy rainfall in the early morning over the Korean peninsula during episodes of cloud clusters associated with mesoscale troughs (CCMTs). For this study, nine episodes with a maximum hourly rainfall amount in the early morning (i.e., 0300-0900 LST) are selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
(29 reference statements)
0
13
1
Order By: Relevance
“…8b). Environmental conditions for CCMT-S have already been reported by Shin et al (2019). As regards CCMT-M, an MCS occurred over the Yellow Sea at about 2100 UTC 15 July and developed into a CC after 2300 UTC slowly moving northeastward.…”
Section: Ccmt Case Studymentioning
confidence: 68%
See 4 more Smart Citations
“…8b). Environmental conditions for CCMT-S have already been reported by Shin et al (2019). As regards CCMT-M, an MCS occurred over the Yellow Sea at about 2100 UTC 15 July and developed into a CC after 2300 UTC slowly moving northeastward.…”
Section: Ccmt Case Studymentioning
confidence: 68%
“…It is well known that transport of humid low-level air from the south or southwest by strong low-level wind is a key element for the occurrences of heavy rainfall over the Korean peninsula and southwestern Japan (e.g., Park et al 1983;Ogura et al 1985;Jeong et al 2016;Kato 2018;Shin et al 2019). Ninomiya and Yamazaki (1979) suggested that the generation of convective instability in the heavy rainfall area within the Baiu front was mainly due to the warm-moist advection in the lower layers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations